N-myc mRNA forms an RNA-RNA duplex with endogenous antisense transcripts. - Krystal, G W (1990)
Nuclear runoff transcription studies revealed nearly equivalent sense and antisense transcription across exon 1 of the N-myc locus. Antisense primary transcription initiates at multiple sites in intron 1 and gives rise to stable polyadenylated and nonpolyadenylated transcripts. This pattern of antisense transcription, which is directed by RNA polymerase II, is independent of gene amplification and cell type. The nonpolyadenylated antisense transcripts have 5' ends which are complementary to the 5' ends of the N-myc sense mRNA. We determined, by using an RNase protection technique designed to detect in vivo duplexes, that most of the cytoplasmic nonpolyadenylated antisense RNA exists in an RNA-RNA duplex with approximately 5% of the sense N-myc mRNA. Duplex formation appeared to occur with only a subset of the multiple forms of the N-myc mRNA, with the precise transcriptional initiation site of the RNA playing a role in determining this selectivity. Cloning of each strand of the RNA-RNA duplex revealed that most duplexes included both exon 1 and intron 1 sequences, suggesting that duplex formation could modulate RNA processing by preserving a population of N-myc mRNA which retains intron 1.